Variability of oxidative stress biomarkers in hemodialysis patients. (March 2014) - Dahwa, Rumbidzai; Fassett, Robert G.; Wang, Zaimin; Briskey, David; Mallard, Alistair R.; Coombes, Jeff S.
Abstract Oxidative stress biomarkers may have a role in the future to assist clinical decisions regarding the use of antioxidant therapies and their efficacy. The aims of this study were to evaluate the within and between-individual variability of plasma oxidative stress biomarkers and investigate factors affecting their variability. Plasma F2-isoprostanes and protein carbonyls were measured in 14 hemodialysis patients every 2 weeks for 10 weeks. Within-individual coefficients of variation (CVs) were isoprostanes = 30.4% (range = 6.1–66.7%) and protein carbonyls = 16.3% (8.4–29.5%). Between-individual CVs were isoprostanes = 34.4% (28.9–40.2%) and protein carbonyls = 19.5% (15.6–24.5%). There were no significant (p > 0.05) relationships between the oxidative stress biomarkers and dietary antioxidant intake, medications, clinical and demographic parameters.